Alterations in functional connectivity of executive control network reveal influence of indoor toluene on cognition at low concentration. (15th March 2023) - Zhan, Changqing; Liu, Junjie; Cui, Mingrui; Wu, Wenjuan; Hao, Fangfang; Wang, Zukun; Liu, Jie; Zhang, Xin; Pan, Liping; Deng, Meili; Su, Xiao; Wang, Jiajing; et al.
Abstract: Background: The mechanism for indoor toluene on cognition at low concentrations remains unknown. Objective: The present study combines attention network testing (ANT) and electroencephalography (EEG) to investigate the brain network mechanisms associated with indoor low concentrations of toluene exposure. Methods: 22 healthy volunteers were exposed for 4 h to four conditions of toluene (0 ppb, 17.5 ppb, 35 ppb, and 70 ppb). Upon exposure to toluene, electroencephalographic activity was recorded and attention network tasks were performed. In this study, the direction transfer function (DTF) has been used to evaluate human brain functional connectivity among neural EEG signals. Results: We have evaluated the results of twenty-two subjects who completed all experiments. No significant difference was found between the four toluene conditions in behavioral performance. The DTFs indicated that the frontal cortex is the main brain region of the executive control network. In the 70 ppb condition, theta band DTF values were significantly higher than those in the 0 ppb and 17.5 ppb conditions. Theta band DTF values from the frontal region to other brain regions (DTFs_outflow ) in 70 ppb condition were higher than in 0 ppb condition. Conclusion: Theta band functional connectivity in the frontal region was significantly enhanced after exposure to toluene at low concentrations. The alternations in neural connectivity demonstrated that more effort was required to accomplish the same tasks when exposed to toluene. These results enable us to understand the early effects of indoor pollutants on cognition and the brain network mechanism. Highlights: A 70-ppb toluene exposure can change functional connectivity of executive control network in healthy subjects. Clarity the potential mechanism for the negative effect of short-term exposure to indoor air toluene on cognition at 70-ppb.